Spatially resolved measurements of electrochemically induced spillover on porous and microstructured Pt/YSZ catalysts - Imbihl, R.; Janek, Jürgen; Justus Liebig University Giessen (My University, 2000)
Pt/YSZ electrodes prepared from platinum (Pt) and yttria-stabilized zirconia (YSZ) can be applied in electrocatalytic experiments for the promotion of different heterogeneously catalyzed reactions. The strong increase in catalytic activity of Pt/YSZ assemblies on electrochemical polarisation has recently been attributed to the creation of catalytically active spill-over species under non-equilibrium conditions. Our experiments combine locally resolved surface sensitive techniques (SPEM, PEEM) with electrochemical methods in order to resolve the processes at the Pt/YSZ interface and to clarify the nature of the spillover species.
Keywords: Solid electrolyte; Electrocatalysis; YSZ; Platinum; Photoelectron emission microscopy; ddc:540